(3bVjI dHfGf CeGe eLdS GdCef GdfUhU GdcGedI deMGVQ GdLdSGJ GdQSejI (B6-11 (3MRjQGf (B1957/ s - Shamseddin, Muhammad Hussein (3eMeO MSjf TeS GdOjf s ((3OGQ GdLOjO; s, 2007)
This is a full text of the minutes of official meetings in June 1958.
Title translation: The Lebanon Issue in the Security Council. Mohammad Hussein Shamseddin.
Arabic
Keywords: 1950-1960; DS80-90 History of Asia- Lebanon; United Nations Security Council UNSC (3eLdS GdGefs; Lebanon